Personal care products as a potential source of aquatic pollution: Effect of polyvinyl alcohol on physiological and antioxidant responses in Mytilus galloprovincialis - Cristiana Roberta Multisanti; Giorgia Zicarelli; Alessia Caferro; Mariacristina Filice; Jana Blahova; Irene Vazzana; Giuseppe Piccione; Sandra Imbrogno; Caterina Faggio; Federica Impellitteri (Ecotoxicology and Environmental Safety)
A high percentage of the broad spectrum of contaminants in aquatic environments is represented by personal care products (PCPs). Polyvinyl alcohol (PVA) is contained in the formulation of many of these products. The extensive use of PVA caused the annual release of over 65.000 tons into the environment, constituting 1.2 % of particles in the Mediterranean Sea. For these reasons, the study aimed to investigate, for the first time in bivalve species, the possible cytotoxicity implications on non-target species, involved in the human food chain, caused by exposure to two different concentrations of PVA (PVA1: 0.1 mg L−1 and PVA2: 10 mg L−1). Following a fortnight of exposure, cell viability, regulation of cell volume decrease, oxidative stress, and biochemical parameters were evaluated. Moreover, the capability of the animal to produce byssal plaques was observed, representing a novelty for assessing the health status of mussels. The results showed a modification in the regulatory capacity of cell volume, particularly in those exposed to PVA2. An alteration in the superoxide dismutase activity (in PVA2) and in the levels of oxidatively modified proteins (PVA1 and PVA2) was detected in gills. A modification in the byssal plaque production following PVA exposure was also observed. These findings enrich the knowledge about the interaction between PVA and organisms, underscoring further research's need to elucidate the environmental implications.